2012
DOI: 10.1029/2011je004025
|View full text |Cite
|
Sign up to set email alerts
|

Shock barometer using cathodoluminescence of alkali feldspar

Abstract: [1] Color cathodoluminescence (CL) images of unshocked and experimentally shocked sanidine at pressures up to 40.1 GPa showed red-violet emission below 20.0 GPa and blue emission above 20.0 GPa. The phases in these shock-recovered samples were identified as crystalline feldspar for red-violet emitting areas and as diaplectic feldspar glass for blue emitting ones by micro-Raman spectroscopy. CL spectra of these shocked sanidine have emissions at $330, $380 and 400-420 nm of which intensities increase with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 56 publications
7
66
0
Order By: Relevance
“…Such a spectral pattern is characteristic of maskelynite and diaplectic feldspar glass, and undetectable in crystalline plagioclase (Kayama et al. , , ). On the other hand, the CL spectroscopy of the dark portion exhibits only a blue emission band at ~410 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a spectral pattern is characteristic of maskelynite and diaplectic feldspar glass, and undetectable in crystalline plagioclase (Kayama et al. , , ). On the other hand, the CL spectroscopy of the dark portion exhibits only a blue emission band at ~410 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We referred previous data of maskelynite and crystalline feldspar to identify the number and peak position of Gaussian components and emission type (Kayama et al. , ). A chi‐squared test for CL spectral datum of each measured sample was also performed to fit in with the smallest margin of standard error.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhomogeneity is not visible under the polarizing microscope. The weak red-violet maskelynite luminescence and the bright blue luminescence of alkali feldspar are related to shock events [48].…”
Section: Datamentioning
confidence: 99%
“…; White ), despite some studies having suggested that feldspar can be just as useful as quartz (e.g., Kayama et al. ; Jaret et al. ).…”
Section: Introductionmentioning
confidence: 99%